Organic host analogues and the search for life on Mars - Marlow,JJ; Martins,Z; Sephton,MA (INT J ASTROBIOL, 2011)
Mars analogue sites represent vital tools in our continued study of the Red Planet; the similar physico-chemical processes that shape a given analogue environment on Earth allow researchers to both prepare for known Martian conditions and uncover presently unknown relationships. This review of organic host analogues – sites on Earth that mimic the putatively low organic content of Mars – examines specific locations that present particular Mars-like obstacles to biological processes. Low temperatures, aridity, high radiation and oxidizing soils characterise modern-day Mars, while acid–saline waters would have presented their own challenges during the planet's warmer and wetter past. By studying each of these hurdles to life on Earth, scientists can prepare instruments headed for Mars and identify the best locations and approaches with which to look for biological signatures. As our use of organic host analogues becomes increasingly sophisticated, researchers will work to identify terrestrial sites exhibiting multiple Mars-like conditions that are tailored to the distinct mineralogical and physical characteristics of Martian locations. Making use of organic host analogues in these ways will enhance the search for signs of past or present life on Mars.